Emissions Reduction by Combustion Modeling in the Riser of Fluidized Bed Combustor for Thar Coal Pakistan: Thar coal emission reduction by combustion modeling - Butt, Jawad Abdullah; Nergis, Yasmin; Hussain, Ahmad; Sharif, Mughal; Das, Arjan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Pakistan has experienced a protracted electricity shortage for the past few years. However, despite Pakistan’s abundant coal deposits, modern coal combustion technology is still required to reduce emissions. Pakistan is struggling to utilize its energy resources and currently experiencing an electrical shortage of more than 8000 MW. The research study models the combustion performance in a fluidized bed riser using ANSYS FLUENT software to understand the combustion behavior of low-rank Thar coal. A simple circulating fluidized bed (CFB) combustion riser was modeled for computational fluid dynamics (CFD) to study the hydrodynamics of gas-solid flow in a circulating fluidized bed riser to reduce emissions and operating costs. Three different types of risers/combustors geometries were used center flow, counter flow, and parallel flow. The CFD model for the solids segment with a k-e turbulence model and the viscosity of static particles in the gas segment both showed excellent mixing performance. According to the FLUENT data, the riser/combustor maximum temperature is around 1400 K or 1130 o C at the primary burning sector in the bed center. According to velocity contours, the greatest velocity in the center-oriented riser/combustor peaks at 3.3 m/s. The CO and CO2 both mass fraction counters show maximum concentration in the center geometry, whereas lower CO concentration is found in parallel geometry. The lowest level of NOx is established in the parallel geometry at around 15 ppm, whereas the counter contours establish the maximum level of NOx at about 31 ppm. Circulating Fluidized Bed Combustor is found to be the most advantageous and effective technology for producing power from Thar lignite coal and reducing emissions.